Support of adolescents to resist peer pressure and coercion to sexual activity. (20th May 2019) - Mashia, E.O.; van Wyk, N.C.; Leech, R.
Abstract : Aim: The aim of this study was to explore and describe how peer pressure and coercion to sexual activity manifested among adolescents in a district in South African and how primary healthcare nurses could support them to resist it. Background: When adolescents engage in early sexual activity, unplanned pregnancies and sexual transmitted infections become health threats. Notwithstanding the governmental health promotion programmes to improve the sexual health of the youth in South Africa, adolescents are still having unprotected sex and even multiple sex partners. Methods: A constructivist grounded theory study was done. The initial sample consisted of 10 adolescents and nine professional nurses who were selected from six primary healthcare clinics in the identified district. Constant comparative data collection and analysis were done to identify the initial codes that were theoretically saturated through another round of data collection and analysis involving five participants (four professional nurses and one health educator). Findings: The findings of the study refer to the definition of peer pressure and coercion and the relationship between professional nurses and adolescents. Ways to optimize the relationship in order for nurses to substitute for parental shortcomings in guiding adolescents towards responsible sexual behaviour and to address the adolescents' vulnerability regarding peer pressure were identified. Conclusion: Challenging adolescent–nurse interaction incidents were identified that warranted different approaches to build on existing initiatives to improve adolescent‐friendly health services. Implications for nursing practice and policy: Primary healthcare nurses should perform complementary roles to substitute for parents who do not have the skills to guide their adolescent children towards responsible sexual behaviour. Programmes need to be developed to enable nurses to optimize their relationships with adolescents and to deliver services through mobile healthcare units to adolescents where they regular socialize. Management should provide budgets for nurses to use multimedia to interact with adolescents.